1966
DOI: 10.1071/bi9661125
|View full text |Cite
|
Sign up to set email alerts
|

The Inoorporation of [35s]Oysteine into the Proteins of Dough by Disulphide-Sulphydryl Interohange

Abstract: Summary[S6S]Cysteine was added, during mixing, to doughs made from wheat flour, in amounts which did not significantly affect the level of endogenous diffusible sulphydryl compounds in flour and which produced no change in the rheological properties of the dough. The doughs were fractionated by ultracentrifugation and analysis of the distribution of the isotope in the dough fractions demonstrated that [S6S]cysteine was bound to both soluble and gluten proteins by disulphide bonds.[14C]Leucine did not become bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1969
1969
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Possible explanations for the absence of thiol-disulfide interchange reactions may be the low water content and very short reaction times of extrusion. Studies in doughs have shown that the thiol-disulfide interchange reactions require longer periods of mixing time and also require sufficient water (Stewart andMauritzen 1966, Jones andCarnegie 1971).…”
Section: Sds-pagementioning
confidence: 99%
“…Possible explanations for the absence of thiol-disulfide interchange reactions may be the low water content and very short reaction times of extrusion. Studies in doughs have shown that the thiol-disulfide interchange reactions require longer periods of mixing time and also require sufficient water (Stewart andMauritzen 1966, Jones andCarnegie 1971).…”
Section: Sds-pagementioning
confidence: 99%
“…2). Sodium sulfite cleaves S-S bonds in WG (Stewart and Mauritzen, 1966). Negligible peaks were eluted at V 0 for film samples cast from solutions heated at 55, 75, and 95°C (Fig.…”
Section: Gel Permeation Chromatographymentioning
confidence: 99%